Parent and Child Characteristics Associated with Child Sunburn and Sun Protection Among U.S. Hispanics. Issue 3 (May 2017) - Day, Ashley K.; Stapleton, Jerod L.; Natale‐Pereira, Ana M.; Goydos, James S.; Coups, Elliot J.
Abstract: Background/Objectives: Skin cancer incidence has been increasing in U.S. Hispanics over several decades and the postdiagnosis outcomes are worse for Hispanics than for non‐Hispanic whites. Parents are influential in children's health preventive behaviors, but little is known about parental factors associated with children's skin cancer–related behaviors in the U.S. Hispanic population. The present study examined parental and child correlates of skin cancer–related behaviors (sunburns, sunbathing, sun‐protective clothing use, and sunscreen use) of children of Hispanic parents. Methods: This survey study included a population‐based sample of 360 U.S. Hispanic parents (44.8% male) who had a child 14 years of age or younger. Measures included parental reports of parent and child demographic characteristics, parent skin cancer knowledge and linguistic acculturation, and parent and child skin cancer–related behaviors. Results: Approximately 28% of children and 31.9% of parents experienced at least one sunburn in the past year and approximately 29% of children and 36.7% of parents were reported to sunbathe. Moderate use of sun‐protective clothing and sunscreen was reported for parents and their children. Child sun‐protective clothing use and sunscreen use, sunburns, and sunbathing were associated with the corresponding behaviors of their parents. Conclusions: Future research should consider the role of acculturation and perceived risk in the sun protection behaviors of U.S. Hispanic children, particularly in those who report a fair skin type. Hispanic parents should be included in interventions targeting their children's skin cancer–related behaviors, and it is suggested that such interventions could also encourage parents to improve their own behaviors.